Food insecurity and healthcare decision making among mobile food pantry clients in Tampa Bay. Issue 3 (4th May 2018) - Bradley, Sarah; Vitous, C. Ann; Walsh-Felz, Aria; Himmelgreen, David
ABSTRACT: This article examines the relationship between food insecurity and health-care decision-making among mobile food pantry clients in Tampa Bay, Florida. Results show a high rate of food insecurity, high stress levels, and chronic health conditions among mobile pantry clients, many of whom are long-term users of food pantry services. The fruits and vegetables supplied by the pantry allow clients to manage chronic health conditions and mitigate some of the financial burden of health-care costs. Research was conducted in cooperation with the Anthropology Department at the University of South Florida, Feeding Tampa Bay, and WellCare .